Virtual learning environment - Aleshidi, Hamad A.; Zeki, Akram M. (IIUM Press, 2011)
The concept of virtual learning environment (VLE) means more than website, it has several features that can enhance the education process, it is not necessary to be represented in distance learning, this concept is extended to enrich the education activities even in the classroom. The current research aims to explore the definitions of the VLEs in literature, furthermore, to explain the main features that may introduce effective VLEs. The tools of VLEs vary when it comes to knowledge representation but the must be rich in pedagogical approaches.